2017
DOI: 10.1002/ehf2.12144
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure awareness survey in Germany: general knowledge on heart failure remains poor

Abstract: AimsPrevious studies demonstrated poor public awareness of heart failure (HF) compared with myocardial infarction and stroke. With respect to several activities to improve HF awareness in recent years, we present data on the development of HF awareness and information sources in Germany over 8 years.Methods and resultsIn 2007, 2012, and 2015, respectively, 2531, 359, and 171 respondents answered questions about causes, presentation, prognosis, and treatment of HF from a survey developed by the German Competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
4
15
0
4
Order By: Relevance
“…This resonates with another finding stating that staggering 56% of the respondents were not aware of HF patients having worse life expectancy after the first hospitalization than the majority of patients with cancer. A similar finding was discovered in other countries and the SHAPE study [3,4,19].…”
Section: Knowledge About Hfsupporting
confidence: 90%
See 2 more Smart Citations
“…This resonates with another finding stating that staggering 56% of the respondents were not aware of HF patients having worse life expectancy after the first hospitalization than the majority of patients with cancer. A similar finding was discovered in other countries and the SHAPE study [3,4,19].…”
Section: Knowledge About Hfsupporting
confidence: 90%
“…The most prominent misconception was that one third of respondents considered that HF is a natural consequence of aging. Interestingly, other studies reported similar results [3,4,19]. This resonates with another finding stating that staggering 56% of the respondents were not aware of HF patients having worse life expectancy after the first hospitalization than the majority of patients with cancer.…”
Section: Knowledge About Hfsupporting
confidence: 71%
See 1 more Smart Citation
“…There is still insufficient awareness of the importance and severity of HF . Increasing awareness and adherence to treatment is a major component of all disease management programmes.…”
Section: Disease Managementmentioning
confidence: 99%
“…We continue to gain more insight into these HF syndromes from contemporary registries [4][5][6]. While one-year and five-year mortality rates of patients with HF remain unacceptably high at about 15% and 50%, respectively [7][8][9][10], awareness about HF management and prognosis in the general population is still low [11].…”
Section: Article Migaj Et Al See P 1064mentioning
confidence: 99%